Stepwise design, synthesis, and in vitro antifungal screening of (Z)-substituted-propenoic acid derivatives with potent broad-spectrum antifungal activity - Khedr MA (Dove Medical Press, 2015)
Mohammed A KhedrDepartment of Pharmaceutical Chemistry, Faculty of Pharmacy, Helwan University, Cairo, EgyptAbstract: Fungal infections are a main reason for the high mortality rate worldwide. It is a challenge to design selective antifungal agents with broad-spectrum activity. Lanosterol 14α-demethylase is an attractive target in the design of antifungal agents. Seven compounds were selected from a number of designed compounds using a rational docking study. These compounds were synthesized and evaluated for their antifungal activity. In silico study results showed the high binding affinity to lanosterol 14α-demethylase (-24.49 and -25.83 kcal/mol) for compounds V and VII, respectively; these values were greater than those for miconazole (-18.19 kcal/mol) and fluconazole (-16.08 kcal/mol). Compound V emerged as the most potent antifungal agent among all compounds with a half maximal inhibitory concentration of 7.01, 7.59, 7.25, 31.6, and 41.6 µg/mL against Candida albicans, Candida parapsilosis, Aspergillus niger, Trichophyton rubrum, and Trichophyton mentagrophytes, respectively. The antifungal activity for most of the synthesized compounds was more potent than that of miconazole and fluconazole.Keywords: design, broad antifungal, molecular modeling